Children's Nonverbal Displays of Winning and Losing: Effects of Social and Cultural Contexts on Smiles. - Mui, Phoebe; Goudbeek, Martijn; Swerts, Marc; Hovasapian, Arpine (Journal of Nonverbal Behavior, 2017)
The article focuses on a study which examines the effects of social and cultural contexts on smiles displayed by children during gameplay. Topics discussed include the effects of sociality and culture on adult's smiling behavior and on children's expressions, the distribution of smiles and non-smiles as a function of sociality and culture, for video recordings depicting winning and losing, and the frequency and percentages of smiles observed as a function of sociality, culture and game outcome.